The Influence of the RADEC Learning Model on Elementary School Students' Mathematical Problem-Solving Skills as Reviewed by Gender Differences - Peni, Raisa Okta; Wahyudin (International Conference on Elementary Education, 2025)
This study investigated the influence of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model on elementary school students' mathematical communication skills, considering the factor of gender. The research aimed to determine the effectiveness of the RADEC model, the presence of significant gender differences, and any interaction effects between the learning model and gender in communication abilities. A quasi-experimental design was employed with fourth-grade students from one elementary school in Bandung City, Indonesia, as participants. Data were collected through a five-item essay test on mathematical communication skills and analyzed using descriptive and two-way ANOVA statistics. The results of this study show that there was a statistically significant positive effect of the RADEC learning model on students' mathematical communication skills, with the experimental group achieving higher average scores compared to the control group (77.74 vs. 56.30, p < 0.001). However, no statistically significant difference was found in mathematical communication skills between male and female students (p = 0.693). Furthermore, the study indicated no significant interaction effect between the learning model and gender on mathematical communication skills (p = 0.863). This finding thus points to the effectiveness of the RADEC learning model as a pedagogical approach for enhancing mathematical communication skills for both male and female students in this elementary education context.